Mindsets, Informed Consent, and Research - Jansen, Lynn A. (The Hastings Center report, 2014)
When patients enrolled in early-phase cancer treatment trials are asked later to explain their decision to participate, they often reveal unrealistically high expectations for therapeutic benefit from participation. This phenomenon has given rise to a complex and ongoing debate over the quality and validity of informed consent to these trials. Bioethicists and researchers must better understand these expectations and why research participants so often have them. This article presents a new explanation for this phenomenon by drawing on social psychology research on mindsets and, in particular, on a distinction between deliberative and implementation mindsets.